Digitalization as a Catalyst for Resilience in the Hospitality Sector - Kokkinou, Alinda; Altan, Michel; Dantas, Abdon; Mitas, Ondrej (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
Hospitality organizations are particularly vulnerable to changes in demand caused by disruptive events such as natural catastrophes, geopolitical events, and pandemic diseases. Nevertheless, the development of organizational resilience by hospitality organizations has remained under-explored. The ongoing digitalization trend provides a unique opportunity for hospitality organizations to combine the adoption of digitalization tools with the development of data analytic capability as a way to anticipate disruptive events and mitigate their impact on operations and performance. Through a cross-sectional survey design and using Partial Least Square Structural Equation Modeling, the present study demonstrates that hospitality organizations can improve their organizational resilience by developing data analytic capability. This can be achieved by (1) investing in the digital tools and IT infrastructure that allows them to sense their environment and (2) adapting their organizational infrastructure to quickly be able to use this information in decision-making. A limitation of the study lies in the use of cross-sectional data which limits temporal causality inferences.